Structure and function of PspA and Vipp1 N-terminal peptides:Insights into the membrane stress sensing and mitigation - Buck,M; Mcdonald,C; Jovanovic,G; Wallace,BA; Ces,O (BBA Biomembranes, 2016)
The phage shock protein (Psp) response maintains integrity ofthe innermembrane (IM) in responsetoextracytoplasmic stress conditionsand is widely distributed amongstenterobacteria. Its central componentPspA, a member of the IM30 peripheral membrane protein family, acts asa major effector of the systemthrough its direct association with the IM. Under non-stress conditions PspA also negatively regulates its own expression via direct interaction with the AAA+ ATPase PspF. PspA hasa counterpart in cyanobacteria calledVipp1, which is implicated in protection of the thylakoid membranes. PspA’s and Vipp1’s conservedN-terminal regions contain a putative amphipathic helix a (AHa) required for membranebinding.Anadjacent amphipathic helix b (AHb) in PspAis required for imposing negative control uponPspF.Here, purified peptides derived from the putative AH regions of PspA and Vipp1were used to directly probe their effectorand regulatory functions.We observed direct membrane-binding of AHaderived peptides and an accompanying change in secondary structure from unstructuredto alpha-helical establishing them as bonafidemembrane-sensing AH’s. The peptide-binding specificitiesand theireffects on membrane stability depend onmembrane anionic lipid content and stored curvature elastic stress,in agreement withfull length PspA and Vipp1 proteinfunctionalities. AHbof PspA inhibited the ATPase activity of PspF demonstratingits direct regulatory role. These findings provide new insight into the membrane binding and function of PspA and Vipp1and establish that synthetic peptides can be used to probe the structure-function of the IM30 protein family.